Rancang Bangun Aplikasi Pencatatan Penerimaan dan Pengeluaran Beras Pada Sub Divre Bulog Surabaya Utara - Abdillah, Muhammad Hamdani; Sudarmaningtyas, Pantjawati; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
The recording of receipts and expenditures rice not in orderly and daily process proceeds or spending rice to the next part of public services will be made a report to be submitted to Kasubdivre, but in reality the process of submitting a report conducted by the warehouse to the public service is not be done directly because the distance between the warehouse with a separate main office so that the reporting process becomes obstructed. The process of collecting the data in hardcopy may caused the data to be lost or damaged and the time data management processes often occur one to write the value so that when confirmed to parts of the public service should seek or revise error, recording error occurs when the revenue and expenditure of rice on the report, it will be very difficult to search and sort the data if all are still done manually in the form of archives. It also takes quite a lot of time. With the problems it required application to recording of receipts and spending of rice that are designed to help the warehouse in terms of doing rice recording entry and exit as well as part of the public service in terms of reporting and as a reference for the procurement of rice, find a reportÂ the number of entry and exit rice, origin and destination of rice, and the number of stocks in each warehouse.Â Keywords : the recording of goods, revenue and expenditure , warehouse.